2003
DOI: 10.1210/me.2002-0217
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Properties and Advantages of a Novel Peroxisome Proliferator-Activated Protein γ Selective Modulator

Abstract: Antidiabetic thiazolidinediones (TZDs) and non-TZD compounds have been shown to serve as agonists of the peroxisome proliferator-activated receptor gamma (PPARgamma). Here, we report the identification and characterization of a novel non-TZD selective PPARgamma modulator (nTZDpa). nTZDpa bound potently to PPARgamma with high selectivity vs. PPARalpha or PPARdelta. In cell-based assays for transcriptional activation, nTZDpa served as a selective, potent PPARgamma partial agonist and was able to antagonize the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
248
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(276 citation statements)
references
References 43 publications
21
248
1
6
Order By: Relevance
“…Telmisartan and irbesartan act as selective modulator of PPAR γ and selective gene regulation, which then triggers specific metabolic effects in vitro (37)(38)(39). Analysis of PPAR γ protein conformation using protease protection has shown that telmisartan and irbesartan directly interact with the receptor, producing a different conformational change than pioglitazone (8).…”
Section: Discussionmentioning
confidence: 99%
“…Telmisartan and irbesartan act as selective modulator of PPAR γ and selective gene regulation, which then triggers specific metabolic effects in vitro (37)(38)(39). Analysis of PPAR γ protein conformation using protease protection has shown that telmisartan and irbesartan directly interact with the receptor, producing a different conformational change than pioglitazone (8).…”
Section: Discussionmentioning
confidence: 99%
“…SPPARgMs would separate the effects of PPARg on lipid and glucose metabolisms as well as on different organ systems (gastrointestinal, immune, cardiovascular). The selective action of such compounds is thought to depend on different structural configurations induced in the ligand-binding domain by their interaction with the receptor, allowing recruitment of different complexes of cofactors that impact on the activation or repression of specific sets of target genes in different tissues [146,218,[226][227][228][229][230][231].…”
Section: Selective Pparg Modulators: a Better Alternative?mentioning
confidence: 99%
“…[25][26][27]. More recently, identification and characterization of specific PPARc ligands known as SPPARMs (Selective PPARc Modulators), displaying beneficial antidiabetic action with no or reduced side-effects, are gaining interest [28][29][30].…”
Section: Introductionmentioning
confidence: 99%